«Leisure should be intellectual!»: studying the preferences of popular science journals readers in the late Soviet period based on the journal «Nauka i zhizn’» materials - Chernyshev, Aleksandr A.; Karpov, Egor K.; Mensh, Elena A. (Journal of the Belarusian State University. History, 2026)
This article analyses the intellectual leisure activities of readers of popular science publications in the late Soviet period. The readership preferences of popular science publications of the Soviet period are examined using materials from the journal «Nauka i zhizn’». It is revealed that in the late Soviet period, the audience of popular science journals, in particular journal «Nauka i zhizn’», showed an increased interest in the contemporary achievements of the Soviet scientific and technological complex. It is emphasised that popular science journals acted as an effective channel for the transmission of scientific information and contributed to maintaining a high level of scientific literacy among the population.